Kepuasan Pengunjung Terhadap Taman Arena Remaja Sebagai Sarana Rekreasi di Kota Jambi - Rahmat Tri Insani; Imam Buchori (Jurusan Perencanaan Wilayah dan Kota, 2020)
Green Open Space (RTH) is an elongated area / path and / or group, the use of which is more open, a place to grow plants, both those that grow naturally and are intentionally planted. One form of public space can be in the form of Green Open Space, namely parks. In urban areas located in the city of Jambi, the Arena Youth Park is a newly renovated park and there are additional tourist facilities for residents' recreational facilities managed by the Jambi City Government. However, to support the Arena Youth Park as a recreational facility, it is necessary to know the level of community satisfaction related to the Arena Youth Park as a recreational facility for the citizens of Jambi City. The purpose of the study was to determine the level of visitor satisfaction with the youth park as a recreational facility in the city of Jambi. In this study there are 2 methods, namely Customer Satisfaction Indexs and Imporance Performance Analysis. The purpose of the Customer Satisfaction Index (CSI) method is to find out the level of consumer satisfaction in the context of this study, namely park visitors to all the attributes in the Taman Arena Remaja while the Importance performance Analysis (IPA) method aims to determine the priority of improvements to the attributes used in the study. The results of the study using the Customer Satisfaction Index (CSI) method showed that visitors to the Arena Arena Remaja were quite satisfied with the condition of the facilities in the park with a CSI calculation of 68.44% or nearly neutral. While the results of the IPA method are in the form of a Cartesian quadrant where the attributes that must be corrected immediately by the Regional Government in quadrant I with attribute 3 (three) improvement of toilet / wc facilities and attribute 10 (ten) conditions of park lighting facilities. The conclusion of this study is that visitors to Taman Remaja Remaja were quite satisfied with the facilities in the park as a means of family recreation